Effect of vitamin C on neutrophil function after high-intensity exercise - Krause, R.; Patruta, S.; Daxbock, F.; Fladerer, P.; Biegelmayer, C.; Wenisch, C. (European Journal of Clinical Investigation, 2001)
High-intensity exercise leads to an increased risk of upper respiratory tract infections in athletes, which had been related to an exercise-induced impairment of neutrophil function. In this study, several indices of neutrophil function were analysed before and after a biathlon and the effect of oral vitamin C on neutrophil function was determined. Six athletes took 2 g vitamin C daily for 1 week prior to a biathlon and four athletes did not take any supplementation. Neutrophil phagocytosis was analysed by fluorescence microscopy and flow cytometry. Cytosolic calcium kinetics were assessed fluorometrically and neutrophil bactericidal ability was assessed by fluorescence microscopy. Reactive oxygen production was analysed by flow cytometry. Catecholamines were analysed by high-performance liquid chromatography. After high-intensity exercise there were significant reductions in the number of phagocytosed Escherichia coli per neutrophil and in neutrophil bactericidal ability. There was a significant exercise-dependent increase of catecholamines. There was no difference between the two groups of athletes. These results do not support the concept that vitamin C supplementation corrects neutrophil dysfunction after strenuous exercise.